Intensive Care Unit Admission Parameters for Patients with COVID-19 - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: The aim of this study was to determine the factors that may be useful in the early identification of populations that are sensitive to Coronavirus disease-2019 (COVID-19) and the need for intensive care unit (ICU) admission. Methods: In this retrospective cohort study, patients who were hospitalized with COVID-19 and requested intensive care consultation at University of Health Sciences Turkey, Gaziosmanpasa Training and Research Hospital between April 1 and July 1, 2020 were analyzed. Results: Of the 208 patients included in the study, 129 were admitted to the ICU and 79 were not. Patients over the age of 85 were more often admitted to the ICU. The probability of ICU admission increased 2.6 times [odds ratio (OR): 2.687; confidence interval (CI): 95% 1.172-6.1641 in patients with a single comorbidity relative to those with no comorbidity, while this risk increased 9.8 times (OR: 9.825, CI: 95% 2.557-37.749) in the presence of four or more comorbidities. In patients admitted to the ICU, the D-dimer and ferritin levels were higher, and the lymphocyte count was lower (p<0.001), relative to those who were not. Receiver operator characteristic (ROC) analysis gave cut-off values of 520 ng/m L, 765 ng/mL, and 0.89 109/L for ferritin, D-dimer and the lymphocyte count. Conclusion: In addition to male gender and advanced age, a higher number of comorbidities is associated with higher disease severity in patients with COVID-19. It is also believed that a low lymphocyte count, as well as high D-dimer and ferritin levels, may guide clinicians in the early diagnosis of patients who require ICU admission.
Keywords: COVID-19; SARS-CoV-2; coronavirus; intensive care units; admission parameters